The Copyrights Chain in the Digital Curation Process - Keren Barner (International Journal of Digital Curation, 2025)
The internet era, open access movement, image sharing platforms, and mainly the rise of artificial intelligence (AI) emphasise the importance of providing moderated access and licences for the reuse of collections by memory institutes as a key step in the digital curation process.